2004
DOI: 10.2105/ajph.94.5.830
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Changes in Drug and Alcohol Use After Becoming Homeless

Abstract: Becoming homeless plays a role in self-reported substance use. Multiservice treatment programs and tailored interventions for homeless persons are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 19 publications
5
36
0
Order By: Relevance
“…After marijuana, cocaine and heroin were the second and third most commonly used drugs by participants. The highest illicit substance usage rates were reported by homeless participants, which replicate findings of a previous investigation of homeless substance users in Pittsburgh and Philadelphia (11). An unexpected finding was that, overall, the abuse of prescription narcotic medications was most prevalent in the homeless population.…”
Section: Discussionsupporting
confidence: 81%
“…After marijuana, cocaine and heroin were the second and third most commonly used drugs by participants. The highest illicit substance usage rates were reported by homeless participants, which replicate findings of a previous investigation of homeless substance users in Pittsburgh and Philadelphia (11). An unexpected finding was that, overall, the abuse of prescription narcotic medications was most prevalent in the homeless population.…”
Section: Discussionsupporting
confidence: 81%
“…5,6 Mental disorders are prevalent among homeless people, [7][8][9] with substance dependence the most common diagnosis among homeless populations across the Western world, occurring at rates far exceeding those among the general population. [10][11][12][13][14] A recent meta-analysis indicated that up to 59 % of homeless people are alcohol dependent, and 54 % are dependent on at least one illicit drug. 7 Other evidence suggests that more than half of homeless people with a substance use disorder suffer at least one comorbid psychiatric disorder.…”
Section: Introductionmentioning
confidence: 99%
“…including substance use, injection drug use, multiple sex partners, and unprotected sex with casual partners (Aidala et al 2005;Allen et al 1994;Burt et al 2001;Culhane et al 2001;O'Toole et al 2004). For example, in this issue, Wenzel et al (2007) found that African American and Hispanic women who were homeless were much more likely to have had multiple sex partners in the prior 6 months than were housed women, in part because of the effects of physical violence and substance abuse.…”
mentioning
confidence: 99%